An Analysis of the Moral Acceptability of the Inclusion of Transgender Athletes in the Olympic Games - Grandbois, Paige Courtney (Πανεπιστήμιο Πελοποννήσου, 2017)
Speculation on whether the inclusion of transgender athletes in the Olympic Games is fair stems from concerns that female transgender athletes will retain male physiological advantages, attributable to testosterone, and that the effects of testosterone supplementation enhance male transgender athletes’ performances. The aim of this thesis is to critically analyze the moral acceptability of transgender athletes’ participation in the Olympic Games. The literature reviewed serves to contextualize the issue of the inclusion of transgender athletes by providing a historical outline of sex-segregation in sport, gender verification in sport, and transgender policy development in high performance sport. The conceptualization of important terms such as sport, fairness, cheating and Olympism clarifies the ethical issues present in determining if it is fair for transgender athletes to compete in the Olympic Games. Philosophical reflection and the application of intersubjectivity reveal that the exclusion of transgender athletes from the Olympic Games on the notions of fairness is morally indefensible. The resulting analysis supports the argument that there is no reason to exclude transgender athletes from the Olympic Games on such notions. Moreover, this thesis demonstrates that a person’s perspective on the fairness of transgender athlete inclusion is shaped by what one believes the goals of the Olympic Games ought to be. This thesis concludes that the eligibility of transgender athletes should not be solely contingent on physiological factors, but should also be hinged on a defensible moral rationale. Through the lens of intersubjectivity, I argue that the inclusion of transgender athletes advances the Olympic Movement by aligning with the moral aims of the Olympic Games and, in turn, facilitates the diffusion of Olympism.
Keywords: Olympic Games; Olympic athletes; Olympism; Transgender athletes; Ολυμπιακά Αθλήματα; Αθλητές των Ολυμπιακών Αγώνων; Ολυμπισμός; Τρανσέξουαλ αθλητές; Transgender; Inclusion; Olympism; Olympic Games; Intersubjectivity; Τρανσέξουαλ; Συμπερίληψη; Ολυμπισμός; Ολυμπιακά Αθλήματα; Διυποκειμενικότητα